Knowledge sharing and turnover intention of librarians in private university libraries in southern Nigeria - Fasola, Omobolanle Seri; Popoola, Sunday Olanrewaju (Daluang: Journal of Library and Information Science, 2024)
Purpose. This research aims to investigate whether or not knowledge sharing would predict the intention to voluntarily leave a work place of librarians in private universities in southern states of Nigeria. Methodology. The survey research design of the correlational kind was used for this study to test the relationship between the variables. The sampling technique used total enumeration of the 308 librarians in all 46 private universities in Southern Nigeria. The instrument used was a questionnaire which was distributed physically and via Google Forms. The data analysis technique was simple statistics of percentages, mean and standard deviation to answer the research questions and Pearson Product Moment Correlation (PPMC) for the hypothesis. Results and discussion. The results showed that knowledge sharing level of the respondent was high, they shared knowledge using informal channels and face to face interactions accounted for occasions they shared knowledge. It was also revealed that the turnover intention of the librarians was high. The results of the correlation test revealed that there was a negative correlation between knowledge sharing and turnover intention. Conclusions. The research results concluded that there was a significance negative relationship between knowledge sharing and turnover intention. This indicates that when knowledge sharing is high, the turnover intention of the librarians will be low. Improving the knowledge sharing attitudes of librarians through formulation of knowledge sharing policies that encourage knowledge sharing practices will lead to a decrease in turnover intention of the librarians.